Will women’s choice of position in first stage of labor affect labor process? - Rao, Shubha; Sridharan, Shylabhirami; Vasudeva, Akhila; S., Roopa P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Controlling the process of childbirth has disabled the parturient to embrace the most spontaneous position of delivery but constricting her to assume a recumbent position. Objective of this study was to study if alternating comfortable maternal positioning i.e., recumbent and alternative position have any influence in the process of labor, type of delivery, neonatal well-being. Methods: Study conducted an observation study on term pregnant women. Study inclusion criteria included all term pregnant women. Exclusion criteria included multiple pregnancies, preterm patient, severe pre-eclampsia, and eclampsia, preterm premature rupture of membranes, sever intrauterine growth restricted fetus. The measured date were maternal general characteristics, duration of labor process, type of delivery and neonatal outcome. Patients were divided into two groups. Group A - if they spent more than 50% in a recumbent position and Group B - any other alternating position. Results: A total 250 women were equally included in this study. The demographic characteristics were matched in both groups and found no significant difference. In the process of labor, Group B had a difference of 1 hours as compared to Group A and the rate of cervical dilation was also faster in Group B. Both of these variables were found to be statistically significant. However, there were no significant difference in the terms of type of delivery and neonatal outcome. Conclusions: The ancient practice of recumbent position during labor is to be discarded as alternating maternal position during the process of labor may a positive influence on the total duration labor. However even though it may or may not have an influence on the other outcome such as route of delivery and neonatal outcome, it is best to encourage women to move and deliver in the most comfortable position.